Safety and efficacy of honeysuckle therapy for epidermal growth factor receptor inhibitor-related rash: a systematic review and meta-analysis - Li-Feng Liu; Shuang Liu; Jie Jiao; Fang-Yuan Zhang (Frontiers in Pharmacology, 2026)
Background Epidermal growth factor receptor inhibitors (EGFRIs) -related rash is prevalent, and honeysuckle therapy (HT) has been extensively utilized for skin rash. However, high-quality clinical evidence supporting the use of HT for EGFRIs-related rash remains scarce. This study aims to systematically assess the prophylactic and therapeutic effectiveness and safety of HT in managing EGFRIs-related rash. Methods A systematic literature search was performed in six electronic databases from their inception to 25 March 2025 to identify eligible randomized controlled trials (RCTs). Methodological risk of bias was evaluated using the Cochrane RoB 1.0 tool, and the certainty of evidence was graded using the GRADE approach. Meta-analyses were implemented using RevMan 5.4 software. Results Seven RCTs with a total of 534 participants were enrolled. Prophylactically, HT significantly reduced ≥ Grade 2 rash incidence (RR = 0.43, 95% CI: 0.29–0.65, P < 0.001; 2 RCTs) and delayed time to rash onset (MD = 8.87 days, 95% CI: 5.30–12.44 days, P < 0.001; 1 RCT). No significant differences were detected in overall rash incidence (RR = 0.84, 95% CI: 0.69–1.01, P = 0.07; 2 RCTs) or rash duration (MD = −4.43 days, 95% CI: −9.69 to 0.83 days, P = 0.10; 1 RCT). For therapeutic use, HT significantly improved the clinical effective rate of rash management (RR = 1.35, 95% CI: 1.13–1.62, P = 0.001; 5 RCTs). Subgroup analyses confirmed consistent efficacy across single-botanical drug/compound formulations and topical/combined oral–topical administration routes. HT also improved quality of life. No severe HT-related adverse events were documented among studies that reported safety outcomes. Evidence certainty was low to very low. Conclusion Due to the low certainty and very low certainty of evidence, HT may alleviate severe EGFRIs-related rash and improve therapeutic response. High-quality, large-scale, multicenter RCTs with standardized honeysuckle botanical drug formulations, dosages, and outcome measures are urgently needed to validate these preliminary findings and improve clinical generalizability. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/ , Identifier CRD420251035535.